1998
DOI: 10.1021/jp983298c
|View full text |Cite
|
Sign up to set email alerts
|

Thiol−Thione Tautomerism in Thioformic Acid:  Importance of Specific Solvent Interactions

Abstract: Attempts have been made to resolve a discrepancy in the recent literature concerning the thiol−thione tautomerism of monothioformic acid. Whereas Kato et al. (J. Am. Chem. Soc. 1996, 118, 1262) reported that the thione acid [RC(S)OH] exists predominantly in polar solvents at very low temperatures, Jemmis et al. (J. Phys. Chem. A 1997, 101, 7389) found, from ab initio calculations including continuum treatments of the solvent effect, that the thione forms HC(S)OH and CH3C(S)OH are less predominant, irrespec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 27 publications
3
35
0
1
Order By: Relevance
“…At all levels of theories, the calculated free energies show a thermodynamic preference of the keto isomer over the enol isomer, regardless of the electronic nature of the substituents and the acid derivatives. These results are consistent with the previous experimental and theoretical observations [6,7].…”
Section: Relative Energiessupporting
confidence: 94%
See 1 more Smart Citation
“…At all levels of theories, the calculated free energies show a thermodynamic preference of the keto isomer over the enol isomer, regardless of the electronic nature of the substituents and the acid derivatives. These results are consistent with the previous experimental and theoretical observations [6,7].…”
Section: Relative Energiessupporting
confidence: 94%
“…By self-consistent reaction filed (SCRF) calculations; they found that the equilibrium of these intramolecular reactions was only slightly influenced by the solvents of various dielectric constants. Nguyen and coworkers found that the tautomeric barrier of thioformic acid HC(@O)SH in the CH 3 OCH 3 is increased by about 1.5 kcal/mol relative to the reactant complex [7]. Interestingly, the work of Ren et al showed that the tautomerism involving CH 3 OCH 3 not only gives the preference of the enol form in the tautomeric equilibrium, but also significantly lowers the tautomeric barriers by >8 kcal/mol in THF solution [8].…”
Section: Introductionmentioning
confidence: 99%
“…In liquid phase, the two tautomeric forms (thione and thiol) can convert into each other by a direct proton transfer mechanism, a similar case with that reported by Delaere and coworkers [56]. However, a solvent assisted proton transfer reaction [58] is also plausible due to the fact that NH donor and C@S acceptor H bonding sites are available for stable complexes formation which are predicted to greatly decrease the energy barrier height [48].…”
Section: Relative Stability Of the Three Tautomerssupporting
confidence: 73%
“…The thione-thiol tautomeric equilibrium has a significant importance in biochemistry and it has attracted both, experimental and theoretical interest, different tautomers in solid and liquid phase being commonly reported [19,[46][47][48][49][50][51][52][53][54][55][56][57]. For this compound, the presence of thiol tautomers in both syn and anti conformers can be supposed because the barrier to rotation amounts to 0.96 kcal/mol at B3LYP/6-31G(d) level of theory, in gas-phase.…”
Section: Relative Stability Of the Three Tautomersmentioning
confidence: 97%
“…H 2 S complex with phenolic OH group as H-bond donor and sulfur as acceptor to be half as strong as p-CR.H 2 O complex. Delaere et al [37] studied interactions of thiol and thione forms of TFA with polar aprotic solvent dimethyl ether by employing ab initio MO and B3LYP calculations using 6-31G** and 6-311? ?G** basis sets.…”
Section: Introductionmentioning
confidence: 99%